Low molecular weight nucleoside gelator: A novel approach for protein and peptide aggregation inhibition - Johnson, Litty (2019)
Protein and peptide based therapeutics have become one of the most rapidly growing class of therapeutics that have potential to treat human disease. However, their inherent instability limits their application, which in turn minimises their therapeutic potential. Among all the physical and chemical instabilities, protein aggregation has become the major important cause of concern in the biopharmaceutical industry. Several additives are currently employed to prevent this. However, these additives possess several drawbacks such as their ability to denature proteins. Thus, there is a need to develop a novel method for the prevention of aggregation that could extend the shelf life of these biotherapeutics.